P474 Cases of Lymphogranuloma venereum in chicago, IL, July 2016 – April 2017. (14th July 2019) - Tabidze, Irina; Blum, Corinne; Kern, David; Rai, Rajendra; Gaitors, Willie; Hendry, Chad; Guttierez, Joshua; Elazier, Carol; Charles, Matt; Morales, Carlos; Bhatia, Ramona
Abstract : Background: Lymphogranuloma venereum (LGV) is caused by Chlamydia trachomatis (CT) serovars L1–L3. The most recent US outbreak of LGV was in 2016 in Michigan in men who have sex with men (MSM) living with HIV. Methods: To better understand LGV epidemiology in Chicago and increase provider awareness, in 2016, the Chicago Department of Public Health (CDPH) introduced a case-based reporting system for MSM with suspected LGV proctitis. Providers were asked to complete standard forms for adult MSM demonstrating symptoms of proctitis. Demographic/clinical and behavioral risk factors data were abstracted from 7/21/16 - 4/30/17. Rectal specimens found to be positive for CT on nucleic acid amplification testing were submitted for LGV laboratory confirmation. Results: A total of 50 suspect LGV cases were reported to CDPH; 47 specimens were submitted to for further molecular testing: 19 were confirmed to be LGV, 10 were non-LGV/ CT positive, 2 had indeterminate results and 16 were CT -negative. All confirmed cases were from rectal swabs: 21% (4/19) were non-Hispanic Black, 42% (8/19) were non-Hispanic white, 32% (6/19) were Hispanic, and 5% (1/19) were non-Hispanic Asian. The median age was 35 years (range = 21–46 years). Of 19 confirmed cases, 84% (N=16) were HIV (+), and in two cases, HIV was diagnosed at the time of LGV infection. The median CD4 count was 613 cells/ml (range = 311–1170 cells/ml, IQR=238); HIV RNA was <40 copies/ml in 58% (11/19) of cases. Amongst the confirmed cases for which treatment information was available (N=17), all had been empirically treated with doxycycline for 21 days. Conclusion: LGV may be suspected in MSM presenting with proctitis symptoms. These data likely underestimate the true local prevalence of LGV in Chicago since reporting was restricted to symptomatic MSM. Improvements in chlamydia case-based surveillance in key populations are critical given the association with LGV and HIV. Disclosure: No significant relationships.